2013
DOI: 10.1093/chemse/bjt071
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-Specific Satiation With a Pinched Nose and Eyes Closed: Testing the Sensory Modality Specificity of Satiation

Abstract: Sensory-specific satiation refers to the decrease in pleasantness derived from a consumed food relative to other unconsumed foods. In the current study, it was investigated to what extent sensory-specific satiation is modality specific. To this end, 80 female participants ate a preferred snack until full while wearing (or not wearing) a blindfold and/or a nose clip. Impaired vision should impede satiation for the appearance of the consumed test snack. Obstructing olfaction should undermine satiation for the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Liking and wanting were assessed by asking the questions ‘how pleasant was the taste of the soup?’ and ‘how much do you want to eat food with similar taste right now?’, respectively. The scale was anchored with 0 (very unpleasant) and 100 (very pleasant) for liking and 0 (do not want at all) to 100 (want very much) for wanting ( 34 ) . Sweet SSS were calculated separately using the ‘liking’ and ‘wanting’ ratings with the following formula: (pre-soup sweet + pre-soup non-sweet + post-soup non-sweet)/3−post-soup sweet.…”
Section: Methodsmentioning
confidence: 99%
“…Liking and wanting were assessed by asking the questions ‘how pleasant was the taste of the soup?’ and ‘how much do you want to eat food with similar taste right now?’, respectively. The scale was anchored with 0 (very unpleasant) and 100 (very pleasant) for liking and 0 (do not want at all) to 100 (want very much) for wanting ( 34 ) . Sweet SSS were calculated separately using the ‘liking’ and ‘wanting’ ratings with the following formula: (pre-soup sweet + pre-soup non-sweet + post-soup non-sweet)/3−post-soup sweet.…”
Section: Methodsmentioning
confidence: 99%
“…However, although this might be true in many cases, researchers have shown that mechanisms of habituation can help individuals cope with these challenges ( Papies et al, 2012 ). Research on sensory-specific satiety, for instance, has shown that individuals habituate to specific foods while consuming such foods ( Rolls et al, 1981 ; Hetherington, 1996 ) in a modality-specific way ( Havermans and Mallach, 2014 ). Even more interesting, recent research has also found that individuals habituate while imagining the consumption of specific food ( Morewedge et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown in humans that the colour and shape of food also have affect SSS ( 42 ). Therefore, the SSS is specific to the sensory modality ( 48 ). In pigs, studies have shown that feeds that are more diverse in terms of sensory properties increase feed intake ( 22 ).…”
Section: Discussionmentioning
confidence: 99%